Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/14651858.cd011008.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Opioids for the palliation of refractory breathlessness in adults with advanced disease and terminal illness

Abstract: There is some low quality evidence that shows benefit for the use of oral or parenteral opioids to palliate breathlessness, although the number of included participants was small. We found no evidence to support the use of nebulised opioids. Further research with larger numbers of participants, using standardised protocols and with quality of life measures included, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 81 publications
(1 reference statement)
3
103
2
3
Order By: Relevance
“…Characteristics are for trials included in each published meta-analysis 3 6 7

*Negative estimate indicates reduction in breathlessness by opioids compared with placebo.

†Included both trials of systemic and nebulised opioids which were not reported separately.

CHF, congestive heart failure; GRADE, Grading of Recommendations Assessment, Development, and Evaluation; I 2 , proportion of the total variance in effect estimates that are between studies; MD, mean difference; RCT, randomised controlled trial; SMD, standardised mean difference.

…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics are for trials included in each published meta-analysis 3 6 7

*Negative estimate indicates reduction in breathlessness by opioids compared with placebo.

†Included both trials of systemic and nebulised opioids which were not reported separately.

CHF, congestive heart failure; GRADE, Grading of Recommendations Assessment, Development, and Evaluation; I 2 , proportion of the total variance in effect estimates that are between studies; MD, mean difference; RCT, randomised controlled trial; SMD, standardised mean difference.

…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of Barnes et al 7 re-analysed using random effects model and accounting for matched data of crossover trials. In the pooled analysis compared with placebo, systemic opioids reduced breathlessness by a mean 0.32 (95% CI 0.18 to 0.47; p<0.001) SDs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations